Green economy based on sharia maqashid case study in Sorkam Tengah Village, Sorkam District, Tapanuli Tengah Distric - Nasruddin Khalil Harahap; Sawaluddin Siregar; Ali Hardana (Jurnal Mantik, 2023)
The purpose of this study is to briefly examine the meaning of the Green Economy and Maqashid Syariah, with the aim that the knowledge index of the people of Sorkam Tengah Village will be better. This study explains both concepts, the point of which is how to maintain the balance of nature. Towards a greener economy is a sustainable goal for every country, including Indonesia. The application of the Green Economy application can reflect the quality of the environment in Indonesia today. Economic, social, and environmental like an unbroken cycle of architecture. Environmental quality is highly dependent on economic and social output. Maqashid Sharia is a new trend in the study of Ushul Fikh which is developing in the contemporary era. The development of Islamic law in the contemporary era is considered more promising when using the methods contained in Maqashid Syariah. As a discipline of development from ushul fiqh, Maqashid Sharia is now much loved by Islamic jurists for deeper study. Therefore, sufficient information is needed about the literature review that discusses Maqashid Syariah from classical to contemporary times. The type of research used to complete the author's journal is a type of qualitative research considering that the form of data presentation is descriptive in nature, with data sources obtained from the general public. direct and indirect (primary and secondary). A Green Economy implementation model that is applicable, reliable, and comprehensive in Sorkam, must be an economic model that is truly green and relevant to the characteristics of the Indonesian nation based on an Islamic Eco-ethical philosophy that is in harmony with socio-culture. Indonesian people and has a legal basis. The principle of low carbon is basically in line with the maintenance of the soul and mind.